Rotten parents and disciplined children: A politico-economic theory of public expenditure and debt - Zheng Song; Kjetil Storesletten; Fabrizio Zilibotti (University of Oslo, Department of Economics, 2008)
This paper proposes a dynamic politico-economic theory of debt, government finance and expenditure. Agents have preferences over a private and government-provided public good, financed through labour taxation. Subsequent generations of voters choose taxation, government expenditure and debt accumulation through repeated elections. Debt introduces a conflict of interest between young and old voters: the young want more fiscal discipline as they are concerned with the ability to of future governments to provide public goods. We characterize the Markov Perfect Equilibrium of the dynamic voting game. If taxes do not distort labour supply, the economy progressively depletes its resources through debt accumulation, leaving future genereations enslaved. However, if tax distortions are sufficiently large, the economy converges to a stationary debt level which is bounded away from the endogenous debt limit. We extend the analysis to redistributive policies and political shocks. Consistent with the empirical evidence, our theory predicts governement debt to be mean reverting and debt growth to be larger under right-wing than under left-wing governments.
Keywords: D72; E62; H41; H62; H63; 330; Fiscal discipline; fiscal policy; Government debt; intergenerational conflict; left- and right-wing governments; Markov equilibrium; political economy; public finance; repeated voting; Finanzpolitik; Öffentliche Schulden; Politische Entscheidung; Politische Partei; Wahlverhalten; Intergenerative Belastungsrechnung; Public Choice; Schätzung; OECD-Staaten